2020
DOI: 10.1161/circep.120.009090
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lesions Created by a Heated, Saline Irrigated Needle-Tip Catheter in the Normal and Infarcted Canine Heart

Abstract: Background - Inability to eliminate intramural arrhythmogenic substrate may lead to recurrent ventricular tachycardia after catheter ablation. The aim of the present study was to evaluate intramural and full thickness lesion formation using a heated saline-enhanced radiofrequency (SERF) needle-tip catheter, compared to a conventional ablation catheter in normal and infarcted myocardium. Methods - Twenty-two adult mongrel dogs (30-40 kg, 15 normal and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Ablation seeks to destroy viable strands of muscle participating in these reentry circuits or channels. 2,[46][47][48][49] Fibrous scar tissue surrounds areas of both surviving and damaged myocytes and creates the reentry substrate, which can be subendocardial, subepicardial, intramural, or transmural. Portions of reentry circuits commonly extend deep to the endocardium and are a recognized reason for failure of VT ablation.…”
Section: Traditional Ablation For Vtmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation seeks to destroy viable strands of muscle participating in these reentry circuits or channels. 2,[46][47][48][49] Fibrous scar tissue surrounds areas of both surviving and damaged myocytes and creates the reentry substrate, which can be subendocardial, subepicardial, intramural, or transmural. Portions of reentry circuits commonly extend deep to the endocardium and are a recognized reason for failure of VT ablation.…”
Section: Traditional Ablation For Vtmentioning
confidence: 99%
“…A previous trial with a longer needle also observed that needle insertion into the myocardium is relatively safe. 56 SERF ablation can produce very large lesions, 27,34,48 raising concern for a risk to viable myocardium outside of the VT substrate scar and worsening ventricular function. One patient in this study, who had extensive substrate and received the largest number of radiofrequency applications in multiple areas around an extensive infarct scar did develop fatal cardiogenic shock.…”
Section: Safetymentioning
confidence: 99%
“…10 With irrigation now feasible via multiple ports covering a larger surface area along a shorter and smaller-gauge needle, and radiofrequency ablation lesion size primarily generated by resistive and thermal-conductive heating augmented by adding convective heating during radiofrequency, an ingenious synergy has been achieved to allow larger lesions with greater width and depth compared to standard irrigated radiofrequency ablation. 10,12 Should this needle catheter and ablation system fare better than the first needle catheter design, it could truly advance our ability to more effectively manage the most difficult-to-control ventricular arrhythmias, ostensibly averting need for cardiac transplantation, at least among those transplanted primarily for refractory, recurrent ventricular arrhythmias. However, several important caveats should be acknowledged.…”
Section: See Article By Packer Et Almentioning
confidence: 99%
“…10 With irrigation now feasible via multiple ports covering a larger surface area along a shorter and smaller-gauge needle, and radiofrequency ablation lesion size primarily generated by resistive and thermal-conductive heating augmented by adding convective heating during radiofrequency, an ingenious synergy has been achieved to allow larger lesions with greater width and depth compared to standard irrigated radiofrequency ablation. 10,12…”
mentioning
confidence: 99%
“…This catheter has been developed and tested in preclinical models. 18,19 It is likely that this needle ablation catheter is effective through a different mechanism. The larger irrigation volume and heating of the irrigant likely lead to a greater degree of convective heating, rather than resistive heating.…”
mentioning
confidence: 99%